New nomenclatorial changes in the family Dermestidae (Coleoptera) - Háva, Jiři (Acta entomologica slovenica (Ljubljana), 2007)
The following new nomenclatorial acts are proposed: Trogoderma granarium Everts, 1898 (= T. koningsbergeri Pic, 1933 syn. n.); T. pectinicornis Reitter, 1881 (= Hadrotoma argentina Pic, 1906 syn. n.); T. ruficolle Reitter,1881 (= T. thoracicum var. bicoloripes Pic, 1936 syn. n.); Trogoderma obscurum Pic, 1936 stat. n.; Attagenus gounellei (Pic, 1915) comb. n. (= A. brasiliensis Pic, 1923 syn. n.); Megatoma (Pseudohadrotoma) graeseri (Reitter,1887) (= M. graeseri var. latenotata Pic, 1902 syn. n.). The species Megatoma (Pseudohadrotoma) graeseri (Reitter, 1887) is newly recorded from Uzbekistan and Trogoderma obscurum Pic, 1936 from Chile.
Keywords: entomologija; favna; hrošči; taksonomija